2012
DOI: 10.1525/bio.2012.62.12.8
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Technologies and Data Management Practices in Environmental Science: Lessons from Academia

Abstract: Environmental scientists are increasing their capitalization on advancements in technology, computation, and data management. However, the extent of that capitalization is unknown. We analyzed the survey responses of 434 graduate students to evaluate the understanding and use of such advances in the environmental sciences. Two-thirds of the students had not taken courses related to information science and the analysis of complex data. Seventy-four percent of the students reported no skill in programming langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
1
36
1
1
Order By: Relevance
“…Just as bioinformatics has become central to modern molecular biology, ecoinformatics is likely to become more central to ecology (Michener and Jones 2012). Most young environmental scientists appear to be unprepared for using these data sets to their full potential because they lack the needed computational skills, or at least the formal training to do so (Hernandez et al 2012). At its simplest level, I think that a fundamental shift from spreadsheet to database as the default approach to data analysis will be one of the top priorities in the coming decade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as bioinformatics has become central to modern molecular biology, ecoinformatics is likely to become more central to ecology (Michener and Jones 2012). Most young environmental scientists appear to be unprepared for using these data sets to their full potential because they lack the needed computational skills, or at least the formal training to do so (Hernandez et al 2012). At its simplest level, I think that a fundamental shift from spreadsheet to database as the default approach to data analysis will be one of the top priorities in the coming decade.…”
Section: Discussionmentioning
confidence: 99%
“…Few students currently in the aquatic sciences were drawn to the field by the ability to use massive data sets and publish insightful papers without ever going outside. However, we may need to attract such students in the future as our traditional field sites are replaced by virtual ones and the need for strong quantitative skills becomes even more pressing (Hernandez et al 2012). More and more citizens are comfortable living in a digital, virtual, and highly controlled world with little connection to the life-support systems provided by the natural world, so recruiting these students may not be such a difficult task.…”
Section: Maintaining a Functioning Scientific Communitymentioning
confidence: 99%
“…While participating in a 2010 data collection trip, I mentioned EML during a discussion with an ecology grad student and staff technician. Neither was familiar with EML at that time, which subsequent study has shown to be common among ecology graduate students (see Hernandez, Mayernik, Murphy-Mariscal, & Allen, 2012). …”
Section: Case Study #1-center For Embedded Networked Sensing (Cens)mentioning
confidence: 99%
“…A recent publication (Hernandez et al 2012) highlighted the urgent need for training that would allow environmental scientists to take advantage of new technologies and quantitative approaches. Such training would include not only the appropriate analytical approaches but also generalizable informatics skills that aid collaborative use of long-term data.…”
Section: Long-term Perspectives On Lake Science and Managementmentioning
confidence: 99%